PERKAWINAN MENURUT MASYARAKAT ARAB PRA ISLAM - Elya Munfarida (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
Abstract: The abandonment of the historical context of the text in the interpretation of the text, make the text meaning is partial or distorted. For example, in Islamic jurisprudence, particularly those associated with the issue of marriage, there is a concept dzihar, namely equating wife with his mother’s (back). When someone does something like this, then in the study of Islamic law, divorce may fall against his wife. Almost all the products of Islamic law claim this. The question then is why equating wife with her husband's mother's back is to drop the divorce? It is certain that the equation wife with her back is a problem that is not simple, because divorce is a critical issue. And this can only be seen by looking at how the Arab culture to talk about these issues. In a patriarchal Arab society, marriage following the model of ownership (tamalluk). This can be seen from the term used to refer to her husband with Ba'al (Lord, master, master, owner) and his wife with mab'ul (servants, slaves, controlled, owned). This ownership model can be seen in the implementation of various forms of marriage in pre-Islamic society. There are several forms of marriage in the community, such as marriage Safah, al-rahti marriage, marital al-mukti, ordinary marriage, marriage istibda ', mut'ah marriage, and polygamous marriages. All forms of marriage above are in terms of a model of ownership (tamalluk). Although the marriage is considered Safah models provide the freedom of women to have sex with several men and determine who will be the father of her unborn child, but the marriage was in a patriarchal culture base, so when he had entered into the marriage, then the position will remain the mab'ul and the husband's property. With the ownership model, women are in a subordinate position and must have the submission and total devotion to her husband. Conversely, men / husbands have dominant authority to treat her in accordance with her wishes. Keywords: Perkawinan, Masyarakat, Arab, Pra Islam